Explaining the Migration Intentions Of Romanian Youth: Are Teenegers Different? - Monica ROMAN; Maria Denisa VASILESCU (Revista Română de Statistică, 2016)
The paper aims at determining the factors that influence the decision of young Romanians to migrate with the focus on adolescents, as they are the most willing to emigrate. We have used a survey-based analysis of data provided by the Friedrich Ebert Foundation in Romania and logistical regression models in order to estimate the significant factors that motivate young individuals to migrate. The results indicate that age is a relevant factor for the intention of the youth to migrate: the younger a person is, the higher the probability of wanting to emigrate. The use of internet and social class of the family are factors that determine the teenagers’ propensity to migrate, while the feeling of discrimination and the entrepreneurial behaviour are key factors that influence the migration intentions of young adults.